BAG3-related myofibrillar myopathy: focus on its cardiac involvement - Daire, Elise; Panaioli, Elena; Gitiaux, Cyril; Gardin, Catherine; Waldmann, Victor; Bonnet, Damien; Wahbi, Karim; Khraiche, Diala (Frontiers in Genetics, 2025)
Myofibrillar myopathy is a cause of rare and severe pediatric cardiomyopathies. Few descriptions of patients carrying the rare p. Pro209Leu variant in BAG3 and presenting with myofibrillar myopathy are reported in the literature. Most reports originate from neurological teams, while the cardiac phenotype remains poorly described, even though it is crucial for prognosis, as cardiac involvement can significantly influence patient outcomes. We focused on the cardiac phenotype associated with p. Pro209Leu variant in BAG3 and conducted a literature review. We report three patients with severe restrictive cardiomyopathy (RCM) including two with left ventricular hypertrophy. Cardiac symptoms appeared 7 [5–7.5] years after neurological onset and were predominantly right heart failure, with high NT-proBNP levels, and arrhythmic events (atrial flutter, ectopic atrial tachycardia). Cardiac MRI showed biatrial and left ventricular fibrosis. Prognosis was severe, with two deaths. In the reviewed cases, cardiac involvement was present in 75%–77.3% of patients and was diagnosed at an early age. Restrictive cardiomyopathy was the most prevalent phenotype (68%–75%), whereas few patients exhibited hypertrophic cardiomyopathy or borderline QT interval. Arrhythmias were observed in only one patient. Heart transplantation was performed in 25%–31.8% patients from 4 to 8 years old, with some developing secondary neurological symptoms. Most patients lost ambulation, required ventilation support, and exhibited orthopedic involvement. Overall mortality ranged from 18.25% to 50%, with sudden death being the most reported cause. The p. Pro209Leu variant in BAG3 is associated with progressive neurological and cardiac involvement, leading to a poor prognosis. Repeated cardiac screening is recommended in these patients and conversely, neurological progression should be monitored after transplantation in patients initially presenting with isolated RCM.